2013
DOI: 10.1155/2013/524380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Samarium Substitution on the Structural and Magnetic Properties of Nanocrystalline Cobalt Ferrite

Abstract: A series of samarium-substituted cobalt ferrites (CoFe2−xSmxO4 with x=0.00, 0.05, 0.10, 0.15, 0.20, 0.25) was synthesized by the sol-gel method. The structural characterizations of all the prepared samples were done using XRD and FTIR. These studies confirmed the formation of single-phase spinel structure in all the compositions. The increase in the value of lattice parameter with increase in samarium concentration suggests the expansion of unit cell. The Hall-Williamson analysis is used for estimating the ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 29 publications
(38 reference statements)
0
20
0
Order By: Relevance
“…This increase in proportion of non-collinear structure decreases the saturation magnetization. 42 The coercive field shows the similar decreasing trend with increase in Ni content and it varies from 7134-279 Oe at 30K and 2134-225 Oe. This variation of coercivity with Ni content can be explained on the basis of domain structure, critical diameter, strains, magneto crystallite anisotropy and shape anisotropy of crystal.…”
Section: Magnetic Propertiesmentioning
confidence: 76%
“…This increase in proportion of non-collinear structure decreases the saturation magnetization. 42 The coercive field shows the similar decreasing trend with increase in Ni content and it varies from 7134-279 Oe at 30K and 2134-225 Oe. This variation of coercivity with Ni content can be explained on the basis of domain structure, critical diameter, strains, magneto crystallite anisotropy and shape anisotropy of crystal.…”
Section: Magnetic Propertiesmentioning
confidence: 76%
“…However addition of Sm 3+ ions resulted in decreased saturation magnetization and coercivity. Decreased saturation magnetization with an increase in samarium content was also observed for samarium substituted CFO nanopowder synthesized by sol-gel method and this decrease is attributed to the decrease in the net magnetic moment due to the substitution of nonmagnetic ion in the octahedral site [19]. The temperature dependence of magnetization studies of gallium (Ga)-substituted cobalt ferrite (CoGa x Fe 2−x O 4 ) revealed the magnetization increase for lower Ga 3+ content (x=0.2 and 0.4) when compared to pure CFO at low temperature and as the temperature increased from 10 K to 400 K magnetization decreased (x=0.4) [23].…”
Section: Introductionmentioning
confidence: 71%
“…Rare-earth ions substitution into Fe 3+ -site in AB 2 O 4 type spinel ferrites has been reported to induce structural distortion and strain and thus significantly modifies the electrical and magnetic properties [16][17][18][19][20][21]. Rare-earth (Ho, Er, Tm, Yb, Lu) ion doping/substitution into cobalt ferrite tend to decrease the room-temperature magnetization as well as the Curie point [22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these rare earth ions have a huge influence on the magnetic anisotropy of the system making the spinel ferrite as promising materials replacing the hexaferrite or garnets [16, 23]. The partial substitution of Fe 3+ ion by rare earth materials ion into the spinel ferrites structure leads to a structural distortion and induce strain, hence modifies the magnetic and electrical properties remarkably [2426]. Generally, the rare earth ions occupy the octahedral B-sites with limited solubility in the spinel lattice structure due to their large ionic radius.…”
Section: Introductionmentioning
confidence: 99%